National survey questionnaire on the diagnosis and treatment status of Helicobacter pylori in peptic ulcer bleeding disease - Jiang, Zongdan; Ding, Yaokun; Li, Chao; Zhang, Zhenyu (Frontiers in Public Health, 2024)
The Maastricht VI/Florence Consensus and Chinese National Consensus Report provide comprehensive guidelines for treating Helicobacter pylori infection. This study aimed to assess physicians' understanding of and adherence to this consensus in different hospitals.Chinese medical staff attending gastrointestinal conferences across various regions were selected for this study. The questionnaire included: 1. the number of patients with peptic ulcer bleeding in hospitals of different levels annually and the diagnostic methods used for H. pylori; 2. whether routine H. pylori examination was conducted and the specific methods employed; and 3. Treatment plans for H. pylori eradication; 4. The mean follow-up duration after treatment 5. Plans for re-eradication in cases of H. pylori treatment failure.Across all levels of Chinese hospitals, the urea breath test was the most commonly used method for detecting H. pylori infection. Most primary (81.53%), secondary (89.49%), and tertiary (91.42%) centres opted for a 14-day quadruple regimen. The preferred antibiotic regimen at all hospital levels was amoxicillin+clarithromycin, with rates of 63.69%, 58.08 %, and 59.27% in the primary, secondary, and tertiary hospitals, respectively. The rates of H. pylori re-examination were 68.15%, 87.07 %, and 87.46% in the primary, secondary, and tertiary hospitals. If H. pylori eradication failed, hospitals at different levels choose to replace the initial plan.There is a need for an enhanced understanding of and adherence to guidelines for H. pylori among physicians in hospitals at all levels.